Current Instabilities in Vacuum Electron Devices and Semiconductor Avalanche Diodes for Generation of THz Oscillations - Lukin, Kostyantyn; Khutoryan, Eduard; Cerdeira, Hilda A. [UNESP]; Kuleshov, Alexei; Yurchenko, Lidia; Ponomarenko, Sergey (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Two promising methods for generation of THz radiation are presented and discussed. The hybrid bulk-surface modes excited in a cavity with bi-periodic grating have been considered. Such modes appear due to Electrodynamic interaction of the bulk modes with surface-wave resonator modes (i.e., leaky spoof surface plasmon polariton of an open grating). The potential for the effective generation of the THz radiation in a Clinotron by the excitation of the hybrid modes has been demonstrated. Theory of a new instability in reversed biased pn-junctions with impact ionization was developed and applied for investigation of THz oscillators design.
Keywords: Clinotron; current instability in avalanche diode; Diffraction Radiation Oscillator; Hybrid Resonant Mode; THz oscillations